Abyssal Solenogastres (Mollusca, Aplacophora) from the Northwest Pacific: Scratching the Surface of Deep-Sea Diversity Using Integrative Taxonomy - Bergmeier, Franziska S.; Brandt, Angelika; Schwabe, Enrico; Jörger, Katharina M. (Frontiers in Marine Science, 2017)
Solenogastres (Aplacophora) is a small clade of marine, shell-less worm-molluscs with close to 300 valid species. Their distribution ranges across all oceans, and whereas the vast majority of species has been collected and described from the continental shelf and slope, only few species are known from depths below 4000 m. Following traditional taxonomy, identification of specimens to species level is complex and time-consuming and requires detailed investigations of morphology and anatomy – often resulting in the exclusion of the clade in biodiversity or biogeographic studies. During the KuramBio expedition (Kuril-Kamchatka Biodiversity Studies) to the abyssal plain of the Northwest Pacific and the Kuril-Kamchatka trench, 33 solenogaster specimens were sampled from 4830 m to 5397m. Within this study we present an efficient workflow to address solenogaster diversity, even when confronted with a high degree of singletons and minute body sizes, hampering the use of single individuals for multiple morphological and molecular approaches. We combine analyses of external characters and scleritome with molecular barcoding based on a self-designed solenogaster specific set of mitochondrial primers. Overall we were able to delineate at least 19 solenogaster lineages and identify 15 species to family level and beyond. Based on our approach we identified three key lineages from the two regionally most species-rich families (Acanthomeniidae and Pruvotinidae) for deeper taxonomic investigations and describe the novel abyssal species Amboherpia abyssokurilensis sp. nov. (Cavibelonia, Acanthomeniidae) using microanatomical 3D-reconstructions. Our study more than doubles the previous records of solenogaster species from the Northwest Pacific and its marginal seas. Almost all lineages are reported for the first time from the region of the (Northwest) Pacific, vastly expanding distribution ranges of the respective clades. Moreover it doubles the number of Solenogastres collected from abyssal depths on a global scale and underlines the lack of exploratory α-diversity work in the abyssal zone for reliable species estimates in marine biodiversity.